Distress-mediated remodeling of cardiac connexin-43 in a novel cell model for arrhythmogenic heart diseases - Wahl, Carl-Mattheis; Schmidt, Constanze; Hecker, Markus; Ullrich, Nina D. (International journal of molecular sciences, 2022)
Gap junctions and their expression pattern are essential to robust function of intercellular communication and electrical propagation in cardiomyocytes. In healthy myocytes, the main cardiac gap junction protein connexin-43 (Cx43) is located at the intercalated disc providing a clear direction of signal spreading across the cardiac tissue. Dislocation of Cx43 to lateral membranes has been detected in numerous cardiac diseases leading to slowed conduction and high propensity for the development of arrhythmias. At the cellular level, arrhythmogenic diseases are associated with elevated levels of oxidative distress and gap junction remodeling affecting especially the amount and sarcolemmal distribution of Cx43 expression. So far, a mechanistic link between sustained oxidative distress and altered Cx43 expression has not yet been identified. Here, we propose a novel cell model based on murine induced-pluripotent stem cell-derived cardiomyocytes to investigate subcellular signaling pathways linking cardiomyocyte distress with gap junction remodeling. We tested the new hypothesis that chronic distress, induced by rapid pacing, leads to increased reactive oxygen species, which promotes expression of a micro-RNA, miR-1, specific for the control of Cx43. Our data demonstrate that Cx43 expression is highly sensitive to oxidative distress, leading to reduced expression. This effect can be efficiently prevented by the glutathione peroxidase mimetic ebselen. Moreover, Cx43 expression is tightly regulated by miR-1, which is activated by tachypacing-induced oxidative distress. In light of the high arrhythmogenic potential of altered Cx43 expression, we propose miR-1 as a novel target for pharmacological interventions to prevent the maladaptive remodeling processes during chronic distress in the heart.